2019
DOI: 10.21608/ejabf.2019.31015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Histological Studies of Salinity effect on gills and liver of Coptodon zillii in Egypt

Abstract: The good growth performance of tilapia species has been recorded in nearly isosmotic salinities. The present study aimed to evaluate the effect of salinity on the structure of Coptodon zillii, being one of the most salinity tolerant tilapia species. Qaroun Lake looses water by evaporation which affects the water levels of the lake and its salinity, recently was subjected to a sharp rise in salinity degrees, which led to a sharp decrease in the rate of fish production. Histological, histochemical, immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…One of the indicators of poultry metabolic rate is rectal temperature, which rises when birds are exposed to high ambient temperatures. In agreement with this study, betaine supplementation in the diet decreased the respiration rates and rectal temperature, suggesting that betaine sequesters the metabolic rates of heat-stressed birds [19]. When the ambient temperature rises above the panting threshold, the relationship between respiration rate and water loss by panting becomes stronger.…”
Section: Resultssupporting
confidence: 89%
“…One of the indicators of poultry metabolic rate is rectal temperature, which rises when birds are exposed to high ambient temperatures. In agreement with this study, betaine supplementation in the diet decreased the respiration rates and rectal temperature, suggesting that betaine sequesters the metabolic rates of heat-stressed birds [19]. When the ambient temperature rises above the panting threshold, the relationship between respiration rate and water loss by panting becomes stronger.…”
Section: Resultssupporting
confidence: 89%
“…Fish gills are frequently used as bioindicators reflecting water quality and the effects of xenobiotic exposure due to their susceptible structure and direct contact with water (Mallatt 1985 ; Paulino et al 2012 ). In agreement with the previous studies, the Aceta-exposed fish, herein, showed hyperplasia, fusion of secondary lamellae and edematous forms in gills (Figueiredo-Fernandes et al 2007 ; Yoon et al 2015 ; Nofal et al 2019 ; Ghayyur et al 2020 , 2021 ). Furthermore, imid-exposed fish showed the epithelial thickening of gill lamellae and dilatation of congested capillaries (Visoottiviseth et al 1999 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, many histopathological alterations were induced by pollutants and heavy metals caused intensive lesion to mucus tissues in both animals and human [27]. Similarly, a reduction in the distribution of carbohydrates and an increase of collagen amount in the gill and liver in one of the most important fish in Egypt due to different degrees of water salinity [28].…”
Section: Discussionmentioning
confidence: 99%